Pengaruh Virtual Try-On, Information Quality, dan Online Customer Review terhadap Keputusan Pembelian Produk Fashion pada Aplikasi Shopee dengan Perceived Value sebagai Variabel Mediasi - Dani Eka Setiawan; Eko Suseno Hendro Riyadi Matruty (Dinasti Research, 2026)
The complexity of purchasing fashion product online encourage consumers to rely on various digital information sources before making purchase decision. This study aims to examine the effect of Virtual Try-On (VTO), Information Quality, and Online Customer Review on Purchase Decision for fashion products on the Shopee platform, wit Perceived Value serving as a mediating variable. A quantitative approach was employed using a survey of 200 Shopee user who match the research criteria. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The result indicate that Virtual Try-On, Information Quality, and Perceived Value have a positive and significant effect on Purchase Decision, whereas Online Customer Review has no significant direct effect on Purchase Decision. Furthermore, Virtual Try-On, Information Quality, and Online Customer Review significantly influence Perceived Value. Perceived Value partially mediates the effect of Virtual Try-On and Information Quality on Purchase Decision, while fully mediating the relationship between Online Customer Review and Purchase Decision. These finding highlight the important role of Perceived Value in explaining how digital information sources shape customers’ purchase decision in the context of fashion e-commerce